Pengembangan Multimedia Interaktif Macromedia Flash Berbasis Keterampilan Berfikir Kritis pada Pembelajaran IPA di Sekolah Dasar - Fitri Daniar; Prima Mutia Sari (Universitas Pendidikan Mandalika, 2022)
The research aims to develop a Macromedia Flash interactive multimedia based on critical thinking for the student in the 2nd class in elementary school. The research used the ADDIE model's R&D (Research and Development). This research was held in SDN Pegadungan 06 Pagi with 26 students and two teachers. The research instruments include was validation sheet and a questionnaire for evaluation. Validation learning media Macromedia Flash is based on critical thinking performed by two experts, validator media and an expert. Techniques analysis data validation used descriptive data analysis. The result showed that the score of validation expert was 64 % in the feasible category, and the score of media validation was 88,3% with very conceivable type. The average of the result teacher response is 97% with the very good category, and the average of the resulting student is 66,4 % % with the good category. The conclusion is that the flash interactive multimedia of Macromedia Flash based on critical thinking on the material natural science is feasible and can be implemented in learning.